2020
DOI: 10.31219/osf.io/wp4zu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data Sharing: a Primer from UKRN

Abstract: Make research data available to ensure transparency and a reliable scientific record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This positive cultural change should now be followed by a coordinated, across-the-board effort by publishers to support open access policies and publishing platforms. Funders, institutions (through subscriptions), and individuals (through targeted outlets) can all incentivise publishers to broaden and improve open access policies as well as other avenues that elevate OaTR practice such as pre-registration; Registered Reports [27,28]; and mandates for sharing data [29], materials, and code [30].…”
Section: Coordinating a Positive Culture Of Open And Transparent Rese...mentioning
confidence: 99%
“…This positive cultural change should now be followed by a coordinated, across-the-board effort by publishers to support open access policies and publishing platforms. Funders, institutions (through subscriptions), and individuals (through targeted outlets) can all incentivise publishers to broaden and improve open access policies as well as other avenues that elevate OaTR practice such as pre-registration; Registered Reports [27,28]; and mandates for sharing data [29], materials, and code [30].…”
Section: Coordinating a Positive Culture Of Open And Transparent Rese...mentioning
confidence: 99%
“…Nonetheless, they are not particularly illuminating to the researcher looking to share their data and analysis code now. An overview of issues involved in making research data available for dissemination can be found in the data sharing primer from UKRN (Towse et al, 2020). Further tangible guidance is available in recently published tutorials such as Klein, Hardwicke, Aust, Breuer, Danielsson, Hofelich Mohr, Ijzerman, Nilsonne, Vanpaemel and Frank (2018), as well as the inaugural issue of Advances in Methods and Practices in Psychological Science (Challenges in Making Data Available, 2018).…”
Section: Good Practice In Reproducibilitymentioning
confidence: 99%
“…Low reproducibility was primarily due to unavailable, incomplete, or ambiguous data, as well as unclear analytic pipelines, an issue compounded by a lack of scripting in a statistical language such as R. However, estimated reproducibility was around 70% for 2018. It appears that open research practices are increasingly being adopted -a shift attributable to changes in academic norms, journal requirements, and technological capabilities.There are several advantages to open data, code, and materials (Towse et al 2020). Innovation is promoted through the re-use of data and code.…”
mentioning
confidence: 99%
“…There are several advantages to open data, code, and materials (Towse et al 2020). Innovation is promoted through the re-use of data and code.…”
mentioning
confidence: 99%
See 1 more Smart Citation